MAGDALENA CHORI RAHMAWATI - admin, Keguru (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2019)
AbstractThis study aims to study the participants' Professional Pedagogical Content Knowledgeand to know the effectiveness of PPG in achieving the goals of achieving pedagogical andprofessional teacher competencies, especially in social studies learning. The research wasconducted with a qualitative method at the PPG Prajabatan held at the Atma JayaCatholic University of Indonesia PGSD Study Program. The research instrument used wasin the form of questionnaires, interviews, and documentation. The results showed thatPPG students generally had a good self-assessment of their PCK abilities, but still hadweaknesses in mastering content mastery so they were difficult to understand andovercome learning difficulties or student misconceptions. This research suggests that inworkshops, PPG students do not merely compile or develop learning implementation planssourced from existing textbooks. PPG students should also be given the freedom to developinnovative social studies learning and directed to analyze the possibility of studentanswers both correct answers and misconceptions that occur.